Potential climate impact of retail CBDC models - Niklas Arvidsson; Fumi Harahap; Frauke Urban; Anissa Nurdiawati (Sveriges Riksbank, 2024)
The expansion of digital payment services like retail Central Bank Digital Currencies (rCBDCs) built on innovative ICT infrastructure, notably datacenters, raises questions regarding potential environmental consequences due to electricity consumption. The design of such systems is critical for environmental impact as it scales with multiple actors and complex protocols as well as being influenced by server location and energy sources. In addition to other critical issues related to rCBDCs, understanding its environmental impact is therefore crucial for policymakers if they are to ensure sustainability. This study analyses one potential rCBDC, the Swedish e-krona project, by focusing on design choices and electricity consumption by comparing to existing retail payment services. Findings indicate that the energy use per transaction of the e-krona is comparable to that of card payments. There are, at the same time, significant differences in energy use depending on whether the design of the infrastructure for the e-krona is centralized or decentralized, where a centralized solution tend to be less energy consuming than a decentralized solution. The study has deployed a lifecycle perspective to explore energy consumption scenarios across various ledger infrastructures enabling a comprehensive assessment.
Keywords: E58; O38; P44; Q58; 330; Energy Consumption; Climate Impact; Digital Payment; E-krona; rCBDC